Perkembangan Islam di Asia Tenggara: The development of Islam in Southeast Asia - Febriyanti, Intan; Indah Ramadani; Sarah Widya Astuti; Hudaidah; Risa Marta Yati (Indo Publishing, 2025)
This study discusses the development of Islam in Southeast Asia, which has undergone significant dynamics since the 13th century through trade routes, proselytizing, and political power. The main issue in this study is how the process of Islamization took place in various regions such as Indonesia, Malaysia, and the Philippines, as well as the factors that influenced the acceptance of Islam amid local cultural diversity. The purpose of this study is to analyze the patterns of dissemination, the roles of scholars and traders, and the socio-political impact of the development of Islam on Southeast Asian societies. The method used is a literature study with a historical-comparative approach, utilizing primary and secondary sources in the form of classical manuscripts, travelogues, and modern academic research. The results of the study show that the development of Islam in this region is not uniform, but is influenced by different local contexts, resulting in a moderate form of Islam that is adaptive to local cultures and plays a major role in the formation of social and political identities in Southeast Asia.